Assessing Consumer Gratification in financial services - Dr. Rahul Raj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Establishing and handling relationships with clients is crucial in the new, aggressive marketplace where businesses must compete for existence. Client fulfillment is the cornerstone of any lasting connection. The evaluation is given even more weight in the service sector since the construct of pleasure is linked to the relationship one has with the service provider. This essay provides a methodology for measuring how satisfied consumers are with banking services, with a particular emphasis on an Indian bank.